2012
DOI: 10.4103/0378-6323.90949
|View full text |Cite
|
Sign up to set email alerts
|

Segmental vitiligo: A randomized controlled trial to evaluate efficacy and safety of 0.1% tacrolimus ointment vs 0.05% fluticasone propionate cream

Abstract: Both tacrolimus and fluticasone propionate produce variable but overall unsatisfactory repigmentation in segmental vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…We analyzed 46 studies involving 1499 patients to evaluate treatment response to TCI therapy (Table 2); 36 studies with 941 patients were included in the TCI monotherapy group and 12 studies with 558 patients were in the TCI plus phototherapy group . The median duration of treatment was 3 months (range, 2-7 months).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed 46 studies involving 1499 patients to evaluate treatment response to TCI therapy (Table 2); 36 studies with 941 patients were included in the TCI monotherapy group and 12 studies with 558 patients were in the TCI plus phototherapy group . The median duration of treatment was 3 months (range, 2-7 months).…”
Section: Resultsmentioning
confidence: 99%
“…The median duration of treatment was 3 months (range, 2-7 months). An at least mild response (≥25% repigmentation) to TCI monotherapy was achieved in 55.0% (95% CI, 42.2%-67.8%) of 560 patients in 21 studies (Figure 2) (Table 3) (eFigure in the Supplement), an at least moderate response (≥50% repigmentation) was achieved in 38.5% (95% CI, 28.2%-48.8%) of 619 patients in 23 studies, and a marked response (≥75% repigmentation) was achieved in 18.1% (95% CI, 13.2%-23.1%) of 520 patients in 19 studies . In children, an at least mild response to TCI monotherapy was achieved in 66.4% (95% CI, 43.2%-89.7%) of 162 patients in 5 studies, and a marked response to TCI monotherapy was achieved in 31.7% of patients (31.7%; 95% CI, 6.7%-56.8%) in 5 studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khalid applied 0.05% clobetasol propionate to treat 23 patients, there were mild atrophy in four cases, telangiectasia in two case, and acneiform papules in two participants [5]. There is mounting evidence showed that atrophy,telangiectasia, hypertrichosis, and acneiform eruptions may develop when topical corticosteroids were used, and this side effect hampers their use, especially when the face is involved [67891011]. In this circumstance, topical CIs provide a favorable alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Клинически эффективно и безопасно было применение такролимуса в терапии проявлений красного плоского лишая на коже и слизистых оболочках, витилиго, как альтернативный вариант терапии стойкой кожной формы эритематоза, очаговой алопеции, розацеа, лимфомы кожи и саркоидоза, других дерматозов [39][40][41][42][43][44][45][46].…”
unclassified